REPLACEMENT COST OF GOODS SOLD. - McCowen, George B. (The Accounting Review, 1937)
Abstract One of the important uses of accounting statistics is to furnish a basis for judgment formation. It is this use which controls the form of accounting statements, the classification of accounts, and the valuations used. Generally speaking, the person with the best information can render the best decision. From this point of view the best accounting would be that which collected and displayed the data in such way that the user would reach the correct decision more frequently than he would if it were collected and displayed in some other manner. If cost prices would cause the user to make the correct decision, cost prices would be the best accounting for that situation. If market prices would cause a better decision, market prices would be the best accounting. Having the above thoughts in mind, It is advocated that the replacement cost of goods sold should be substituted for the cost of goods sold when preparing the profit-and-loss statement of a mercantile or manufacturing concern. By preparing the profit-and-loss statement on a replacement cost basis this expansion policy will be curbed. The merchant will realize that he must recapture replacement cost plus expenses on the upswing and will increase sales prices more rapidly.